PENYELENGGARAAN KEKUASAAN KEHAKIMAN GUNA MENCIPTAKAN PERADILAN YANG BEBAS DAN TIDAK MEMIHAK - Ronny Winarno; Endang Retnowati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
The existence of integrated judges can be an important element in upholding the power of judicial affairs against the interference or the influence from the outsider. The judges have the function to strengthen national union, civilization and democracy. The spirit of professionalism included the fair court and to hold high the name of the race and nation, due to court norm and ethics.